Functional Foods as a New Therapeutic Strategy - Cruz-Chamorro, Ivan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The articles discussed in this reprint show the potential health benefits of nutraceuticals, which are products containing bioactive compounds that can prevent and treat chronic diseases. This book explores various functional ingredients, including plant-derived products, mushrooms, microalgae, and goji berries, for their therapeutic, hypoallergenic, and sporting purposes. The study of the gut microbiome and its interactions with dietary components is also discussed. Additionally, the importance of sustainable and environmentally friendly practices in the food industry also stands out. As consumers seek out natural and functional food products, continued research on and the development of nutraceuticals will be critical in promoting healthy aging and addressing chronic diseases.